Sakral dan Profan (Sistem Kepercayaan Suku Akit di Bantan Tengah) - Sahrul Sori Alom Harahap (STAIN Bengkalis, 2021)
Akit with a belief system that is unique enough to become an interesting discourse, the belief system is